Pengendalian Persediaan Kedelai Sebagai Bahan Baku Produksi Tahu I-Love Bandung - Yanti Budiasih; Asriyal Asriyal (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2014)
The tofu enterprise named 1-Love Bandung is the one enterprise on producing tofu every day by using the soybeans purchased from the cooperative. Reorder the soybeans using a model named a “Kotak System” which is mean that supplies the raw material will be immediately visible in the box that is used as storage. In this way the purchase of raw materials will be made if the amount of raw materials in a box has achieved certain results. This paper reviews: (1) the results of calculations required amount of efficient and optimum raw materials, which is calculated using the Trend Projection and EOQ method; (2) the results of the calculation amount required of safety stock; (3) the Reorder Point of inventory; (4) the maximum inventory; and also (5) the total inventories cost (TIC).